The Relationship between Oil Price Shocks and Macro-economic Activity: Evidence from Selected Asian and European Economies - Al Khusaibi, Shurooq Abdullah Khalfan (2016)
This paper attempts to examine the impact of oil price fluctuations on some of the largest net oil importers and exporters economies in Asia and Europe using a Structural VAR model. The main objective of the paper was to examine how will the macroeconomic response to oil price fluctuations differ depending on the country’s net position in the global market. Prior to conducting the analysis, a unit root test was carried to ensure the stationarity of the data. The unit root test confirms the stationarity of the data at first differences. The impulse response function shows evidence of a significant impact on the countries’ real GDP, inflation and exchange rate with few exceptions in the short-run. In most cases, the influence appears to weaken in the long run. The GCC countries exhibit a very similar pattern in their response. However, the positive shocks display a dissimilarity in its impact to the rest of the countries in the sample. The variance decomposition results further support the charts produced by the impulse response functions. The results generated are compared with existing literature on the selected countries. Finally, some policy implications are suggested based on the results generated from both tests.